(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Tukach I. I. Forming preschoolers valuable attitude to their basic duties as psycho-pedagogical problem. The article analyzes the research on the formation of value treatment of preschool children with their basic responsibilities by outlining the basic concepts of «morality», «duty», «value treatment» in psychological and pedagogical literature.